2015
DOI: 10.1130/l420.1
|View full text |Cite
|
Sign up to set email alerts
|

Orogenic paleofluid flow recorded by discordant detrital zircons in the Caledonian foreland basin of northern Greenland

Abstract: Concordant detrital zircon dates from Neoproterozoic to Paleozoic continental slope and trough deposits in northern Greenland indicate Late Archean and Paleoproterozoic sediment sources. Significant numbers of dates are, however, discordant and, together with a few apparently concordant dates, give ages younger than the depositional ages of overlying fossiliferous sediments. The discordance pattern implies partial or total radiogenic-Pb loss during the Middle Devonian, possibly facilitated by postdepositional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 37 publications
(35 reference statements)
0
11
1
Order By: Relevance
“…It has long been recognized that detrital zircon from metaclastic rocks yields a high proportion of discordant zircon due to postdeposition metamorphism (e.g., Gehrels et al, 1991). Other studies have demonstrated that a high number of discordant analyses may be due to postdeposition alteration (e.g., Morris et al, 2015). In contrast, the high degree of discordance in this study (~40%) reflects the metamorphic character of the source terrane rather than postdepositional processes.…”
Section: Characteristic Signature Of Detrital Zircon From Metamorphiccontrasting
confidence: 64%
“…It has long been recognized that detrital zircon from metaclastic rocks yields a high proportion of discordant zircon due to postdeposition metamorphism (e.g., Gehrels et al, 1991). Other studies have demonstrated that a high number of discordant analyses may be due to postdeposition alteration (e.g., Morris et al, 2015). In contrast, the high degree of discordance in this study (~40%) reflects the metamorphic character of the source terrane rather than postdepositional processes.…”
Section: Characteristic Signature Of Detrital Zircon From Metamorphiccontrasting
confidence: 64%
“…To better understand the most likely timing of radiogenic-Pb loss we model the discordant age data from sample BB5 using a variety of times of assumed Pb loss, with the resultant population compared with concordant data using the K-S statistic following the approach discussed by Morris et al (2015). The approach assumes that the discordant population is derived from a similar geological province with similar zircon age spectra to the concordant zircon population.…”
Section: Discordant Age Datamentioning
confidence: 99%
“…How to handle discordance in detrital zircon data is beyond the scope of the present study, but the problem has been discussed in recent papers by Morris et al . () and Reimink et al . ().…”
Section: Discussionmentioning
confidence: 88%